Proposta de gestão participativa para uso do espaço físico para a cidade universitária da UFSM em Cachoeira do Sul (RS) - Farias, Graziano Franceschet (2021)
Higher education in Brazil, until the 1960s, was concentrated in capitals and coastal regions of the country, therefore, taking an undergraduate course was a privilege for people with greater purchasing power or who lived in such places. In order to internalizing public higher education in Brazil, Professor Mariano da Rocha and his team created the University of Santa Maria - USM, created by Law n. 3,834 – C of December 14, 1960 and federalized in 1965 in the city of Santa Maria (RS), renamed to the Federal University of Santa Maria – UFSM. In the 2000s, as of the Support Program for Restructuring and Expansion Plans at Federal Universities – REUNI, started in 2007, the brazilian Federal Government was able to provide the population an improvement in the offer of higher education. With REUNI, there was an expansion of the physical structures and courses of federal universities, the formation of new campuses, as well as the creation of various institutions. On the other hand, universities should expand their increase the number of students as well as ensure their permanence in graduation. Taking advantage of this program, UFSM used the opportunity and enlarged, expanded its facilities in the city of Santa Maria (RS) and created new campuses, one of them being the UFSM unit in the city of Cachoeira do Sul (RS), object of this work, in which it is intended, through bibliographical, documental and structured interviews, to analyze, the impacts with the local and internal community, of the institution, the impacts, positive or negative, of the installation of the equipment in the municipality, concluding that there was some improvement in the provision of services and infrastructure in the city, with the population being satisfied with the project and eager to participate in your future. A proposal for a Resolution (product of the dissertation) was also prepared, with changes in the current Internal Regulation for the managing the physical, biotic and socioeconomic aspects of the UFSM university city in Cachoeira do Sul (RS), contemplating the participation of the actors involved: UFSM employees in Cachoeira do Sul (RS) and community leaders, as well as representatives of the Executive and Legislative, municipal and regional powers, in addition to associative and union entities in the city.